2019
DOI: 10.2147/ott.s210117
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prolonged low-dose infusion for gemcitabine: a systematic review</p>

Abstract: Background The present standard dose of gemcitabine (Gem), a pyrimidine antimetabolite, is 1,000–1,250 mg/m 2 , and the infusion time is 30 min. However, pharmacological studies have demonstrated that Gem with prolonged infusion could attain a better accumulation rate of Gem triphosphate (active metabolites of Gem), indicating that Gem with prolonged infusion is superior to 30-min infusion. Thus, this systematic review aims to provide some references for Gem administered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Additionally, low-dose gemcitabine selectively inhibits tumor-associated myeloid-derived suppressor cells in mice bearing 4T1 mammary carcinomas, which is beneficial to the amplification of tumor-targeting T cells ( 20 ). Moreover, a systematic review revealed that, compared with standard-dose infusion for gemcitabine, prolonged low-dose infusion is an effective and well-tolerated regimen for multiple solid tumors ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, low-dose gemcitabine selectively inhibits tumor-associated myeloid-derived suppressor cells in mice bearing 4T1 mammary carcinomas, which is beneficial to the amplification of tumor-targeting T cells ( 20 ). Moreover, a systematic review revealed that, compared with standard-dose infusion for gemcitabine, prolonged low-dose infusion is an effective and well-tolerated regimen for multiple solid tumors ( 21 ).…”
Section: Introductionmentioning
confidence: 99%